The Art of Community : Seven Principles for Belonging. - Vogl, Charles (Berrett-Koehler Publishers, 2016)
Create a Culture of Belonging! Strong cultures help people support one another, share their passions, and achieve big goals. And such cultures of belonging aren't just happy accidents - they can be purposefully cultivated, whether they're in a company, a faith institution or among friends and enthusiasts. Drawing on 3,000 years of history and his personal experience, Charles Vogl lays out seven time-tested principles for growing enduring, effective and connected communities. He provides hands-on tools for creatively adapting these principles to any group'formal or informal, mission driven or social, physical or virtual. This book is a guide for leaders seeking to build a vibrant, living culture that will enrich lives. Winner of the Nautilus Silver Book Award in the Business and Leadership Category.